Pengaruh Content Marketing Instagram Terhadap Customer Engagement Di Khas Ombilin Hotel - Kevin Day Levrant; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
To build content marketing over a long period of term is a important factor to create the engagement with customers. This study has the purpose to unveil the effects of content marketing Instagram upon customer engagement at Khas Ombilin Hotel. This research employed a quantitative, descriptive, causal, and associative style, with a sample size of 204 respondents. To analyze the data in this study, we utilized the SPSS 23 software application. The study employed the variables of content marketing (X) and customer engagement (Y). According to the study, content marketing on Instagram had a significant impact on customer engagement at Khas Ombilin Hotel, accounting for 78% of the influence, as opposed to the remaining 22% attributed to other factors.